PELESTARIAN TRADISI MAKAN BAJAMBA DALAM PENGUATAN NILAI GOTONG ROYONG MASYARAKAT MINANGKABAU DI JORONG BUNGO KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Zikma Zofanda; Jamurin; Ranti Nazmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the preservation of the Makan Bajamba tradition in strengthening the value of mutual cooperation among the Minangkabau community in Jorong Bungo, Koto VII District, Sijunjung Regency. This research employed a descriptive quantitative approach. The informants consisted of niniak mamak, Bundo Kanduang, the youth leader, and community members selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that niniak mamak play a vital role in guiding, supervising, and transmitting customary values to the younger generation. Meanwhile, community members actively participate in every stage of the tradition, including deliberation, preparation, food processing, communal dining, and post-event cleaning. The preservation of the Makan Bajamba tradition serves as a medium for cultural transmission while strengthening the values of mutual cooperation, togetherness, responsibility, social solidarity, and kinship, ensuring its continued relevance within the community.